Mission and Power The relevance of the Edinburgh 2010 discussion in the theological engagement with violence - Cornelius J.P. Niemandt (Verbum et Ecclesia, 2011)
The ecumenical conference in Edinburgh in 2010 identified the issue of Mission and Power as one of the pressing mission themes for our generation. Christian mission has always been associated with power. The promise of the risen Christ was that his followers would receive power when the Holy Spirit came on them. History, unfortunately, recounts how Christian mission became backed by force and violence, the very opposite of the kind of power and energy associated with the Spirit of God. At the Edinburgh 2010 conference this violence in mission was studied as expressed in churches relations with indigenous peoples. This article engages violence theologically and ecumenically by inviting the Edinburgh 2010 discussion into the reflection on violence in the democratic South Africa, as it was presented as a contribution to a wider discussion on violence in South Africa. This is done with the following objectives in mind: (1) to better understand the interplay between violence and power against the background of a broader global and ecumenical discussion of this issue; and (2) to suggest clues for the theological reflection on violence that may help to create a powerless, spacecreating discourse that opens up thinking and contributes to healing and justice.The article concludes by building on the Edinburg 2010 foundations of mission as dialogue and proposing prophetic dialogue as a powerless discourse: Transforming the meaning of mission means that Gods mission calls all people to work together for healing and justice in partnerships of mutuality and respect.